2014
DOI: 10.1017/s0022215114000073
|View full text |Cite
|
Sign up to set email alerts
|

Accidental button battery ingestion presenting as croup

Abstract: This case highlights the difficulty of diagnosing oesophageal foreign bodies. We also discuss the characteristics of button batteries which confer a greater risk of impaction, and the associated sequelae and complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 18 publications
2
10
1
Order By: Relevance
“…This finding is in accordance with previous literature [3, 5, 10]. Animal studies have shown that necrosis of the lamina propria in the esophagus can develop within 15 min and can expand to the outer muscular layer of the esophagus within 30 min after button battery ingestion [13].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is in accordance with previous literature [3, 5, 10]. Animal studies have shown that necrosis of the lamina propria in the esophagus can develop within 15 min and can expand to the outer muscular layer of the esophagus within 30 min after button battery ingestion [13].…”
Section: Discussionsupporting
confidence: 93%
“…The third mechanism is thought to cause the most damage due to hydrolysis, which leads to hydroxide at the negative pole of the battery, which results in a high pH. The mucus membrane touching the negative pole of the battery will be damaged the most [5, 11]. The new lithium 3-V button batteries are even more dangerous than the older 1.5-V button batteries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ingestion, aspiration, and impaction of small, coin-shaped, button batteries account for over 3,300 exposures reported annually to the American Poison Control Centers and can result in clinically morbid and even fatal sequelae [1][2][3][4][5][6][7][8]. In 2013, incidence of button battery ingestions was estimated at 10.5 per million people with a fatality rate of 0.5% [1].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical presentation frequently involves mucosal damage to respiratory or digestive epithelium from direct pressure necrosis, electrolysis, caustic exposures, or possibly heavy metal toxicity. However, atypical and grave sequelae from battery impactions have been described to include pneumonia, tympanic membrane perforation, vertebral osteomyelitis, vocal fold paralysis, trachea-esophageal, aorto-esophageal fistula, and death [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%